2019
DOI: 10.1042/bsr20190855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icariin on long noncoding RNA and mRNA expression profile in the aortas of apoE-deficient mice

Abstract: Objective : The beneficial effects of icariin (ICA) in ameliorating atherosclerosis (AS) are well known, but the underlying protective mechanism has not been fully elucidated. The present study aimed to investigate altered long noncosing RNA (lncRNA) and mRNA expression profiles in ApoE−/− mice after ICA treatment. Method : The atherosclerotic plaque area was evaluated on high-fat diet (HFD)-induced ApoE−/− mice treated with either ICA or vehicle. LncRNA and mRNA integrated microarrays was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It has been reported that CALML3 are involved in cell proliferation and apoptosis ( Bennett et al, 2013 ; Jia et al, 2018 ). Besides, previous studies have suggested that CALML3 may play critical roles in AS development mediated by icariin ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that CALML3 are involved in cell proliferation and apoptosis ( Bennett et al, 2013 ; Jia et al, 2018 ). Besides, previous studies have suggested that CALML3 may play critical roles in AS development mediated by icariin ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…For example, Zhang et al . performed lncRNA-mRNA co-expression analysis in atherosclerosis [ 33 ] and Pant et al . constructed lncRNAs and mRNAs mediated co-expression network in diabetic cardiomyopathy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ethosomal gel of icariin combined with hydroxysafflor yellow A (HSYA), Epimedin B, and 3, 4-dihydroxybenzoic acid could be used to treat peripheral neuropathy caused by oxaliplatin [ 211 ]. Icariin has also been found to exert an anti-atherosclerosis effect by regulating some pathways involving lncRNA (Lon non-coding RNA) and mRNA [ 212 ], suggesting its neuroprotective roles may also be regulated by lncRNA and mRNA.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%